Elektromagnetno polje: učbenik za študente fizike na Fakulteti za naravoslovje in matematiko Univerze v Mariboru - admin; Tkalec, Uroš; Kralj, Samo (University of Maribor Press, 2019)
Electromagnetic Field: a Textbook for Students of Physics at the University of Maribor, Faculty of Natural Sciences and Mathematics. The textbook Electromagnetic field is written particularly for students of physics at the Faculty for natural sciences and mathematics, University of Maribor. It covers all topics from electromagnetism and it is conceptually divided into two parts: for lower and for higher level of complexity. The first part will be useful mostly to the students of first degree, within the subject Electromagnetism, while the second part will be useful to the students of second degree, within the optional subject Electromagnetic field. In many topics, e.g., in electrostatics, the learning material from the second part of the book is a supplementation and much more demanding upgrade of the material from the first part. The aim of the textbook are not predominantly solving calculation exercises, thus we recommend the students to find some additional learning materials, for instance, with several solved problems. Nevertheless, 50 basic problems with all calculation details are given in this book.